Rapid detection of tuna fish oil adulteration using FTIR-ATR spectroscopy and chemometrics for halal authentication - Irnawati Irnawati, Anjar Windarsih, Anastasia Wheni Indrianingsih, Wuri Apriyana, Yuli Ary Ratnawati, La Ode Muhamad Hazairin Nadia, Abdul Rohman (Journal of Applied Pharmaceutical Science, 2023)
High-quality Tuna fish oil (TFO) is vulnerable to adulteration with lower-quality oil such as pork oil (PO) by unethical players for economic reasons. PO is a nonhalal oil that is prohibited to be consumed by certain religions such as Muslim and Jewish. This research aimed to develop rapid authentication methods using Fourier transform infrared (FTIR) spectroscopy combined with chemometrics for the detection of PO in TFO. FTIR spectroscopy provided fingerprint spectra for TFO and PO. TFO demonstrated two peaks at the carbonyl vibration. The peak at 1,710 cm−1 was specific to TFO whereas the peak at 1,032 cm−1 was specific to PO. Partial least square–discriminant analysis (PLS-DA) and orthogonal projections to latent structures–discriminant analysis (OPLS-DA) was successfully used to detect PO adulteration in TFO by discriminating and classifying TFO and TFO adulterated PO, and PO samples with OPLS-DA showed high accuracy (R2X = 0.998, R2Y = 0.735) and good predictivity (Q2 = 0.552). Meanwhile, the concentration of PO in the mixtures of TFO-PO was successfully predicted using PLS and OPLS with high accuracy (R2 = 0.9928) and good precision. OPLS indicated a better model than PLS with lower error evaluated using root mean square error of estimation (RMSEE) and root mean square error of cross-validation (RMSECV). The obtained RMSEE and RMSECV were 2.81 and 2.94, respectively. This developed method could detect the lowest PO (5%) presented in TFO. Therefore, it can be concluded that there was an analytical technique based on FTIR spectra combined with principal component analysis, PLS-DA, and OPLS-DA could be used for halal authentication of TFO. Further, it can be developed for halal authentication of fish oils.